Stromal Cells of the Human Postmenopausal Ovary Display a Distinctive Biochemical and Molecular Phenotype - Jabara, Sami; Christenson, Lane K.; Wang, Clare Y.; McAllister, Jan M.; Javitt, Norman B.; Dunaif, Andrea; Strauss, Jerome F. (The journal of clinical endocrinology and metabolism, 2003)
The stroma of the human postmenopausal ovary is postulated to produce androgens, but evidence for and against this idea exits in the literature. The purpose of this study was to determine whether key steroidogenic enzymes involved in androgen synthesis are expressed in the postmenopausal ovarian stroma. Stromal cells were isolated from postmenopausal ovaries and expression for genes involved in steroidogenesis [steroidogenic acute regulatory protein (StAR), P450scc, 3β-hydroxysteroid dehydrogenase (3β-HSD) P450c17, and P450c27] as well as for several growth factor binding proteins [gremlin, IGF binding protein-4, follistatin, and secreted frizzled-related protein (sFRP)-1 and -4], were compared with cultured human theca cells and dermal fibroblasts. Production of steroids (pregnenolone, progesterone, and hydroxysterol metabolites) and the metabolism of [3H] pregnenolone by ovarian stromal cells were also assessed. Isolated ovarian stromal cells from different subjects had a uniform morphology within and across cultures. Quantitative real time RT-PCR revealed that StAR, P450scc, and 3β-HSD transcripts were, respectively 30, 25, and 45 times more abundant in theca cells than in stromal cells. Mean levels of P450scc and 3β-HSD transcripts in stromal cells were similar to those found in dermal fibroblasts, whereas StAR transcripts in stromal cells were 285-fold more abundant than in fibroblasts. There was no significant expression of P450c17 in ovarian stromal cells or fibroblasts (∼2000-fold less than in theca cells). Western analysis demonstrated the presence of the 30-kDa StAR mature protein in the cultured stromal cells, whereas P450c17 protein was not detectable. Ovarian stromal cells did not metabolize [3H] pregnenolone in the presence or absence of 8-Br-cAMP. Furthermore, pregnenolone and progesterone secretion by stromal cells was also undetectable, even in the presence of 22-hydroxycholesterol. P450c27 protein was detected in ovarian stromal cells and its metabolic products (i.e. 27-hydroxycholesterol and cholestenoic acid) were found in the culture media, reflecting functional cholesterol 27-hydroxylase activity. Follistatin, gremlin, IGF binding protein-4, and sFRP-1 and -4 transcripts were detected in the stromal cells in relative amounts significantly higher than theca cells, but not significantly different from fibroblasts, except for sFRP-1, which was significantly higher in stromal cells. Our observations demonstrate that stromal cells of the postmenopausal ovary have a signature biochemical and molecular phenotype that can be distinguished from fibroblasts. These cells do not appear to have significant steroidogenic potential in vitro, but they do metabolize cholesterol into hydroxysterols. We conclude that the predominant stromal cells of the postmenopausal ovary are not a significant site of androgen biosynthesis.